An UPLC-MS/MS Method for Determination of Osimertinib in Rat Plasma: Application to Investigating the Effect of Ginsenoside Rg3 on the Pharmacokinetics of Osimertinib - Zhenzhen Ying; Jingyao Wei; Ruijuan Liu; Fang Zhao; Yifang Yu; Xin Tian (International Journal of Analytical Chemistry)
Osimertinib is a novel oral, potent, and irreversible epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) for treatment of advanced T790M mutation-positive advanced non-small cell lung cancer, which is commonly combined with ginsenoside Rg3 in clinic to enhance the efficacy and minimize adverse reactions. In the present study, a highly sensitive UPLC-MS/MS method was established and validated for analysis of osimertinib in rat plasma according to US FDA guideline. Separation was performed on a C18 (2.1 × 50 mm, 2.6 μm) column using a gradient elution of ammonium formate (10 mM) with 0.1% formic acid buffer (A) and ACN (B) at a flow rate of 0.2 mL/min. Detection was carried out on a triple quadrupole tandem mass spectrometer equipped with electrospray ionization in the MRM mode. The method was validated over a concentration range of 1–400 ng/mL for osimertinib. The intra- and interday accuracy and precision values were within ±15%. No significant degradation occurred under the experimental conditions in stability assays. There was a further investigation on the effects of multiple doses of ginsenoside Rg3 on the pharmacokinetics of osimertinib in rats for the first time. The results implied that osimertinib exhibited a slow absorption and moderate-rate elimination in rats following oral administration. Coadministeration with ginsenoside Rg3 (5 mg/kg, 7 days, i.g.) may have no effect on the pharmacokinetics of osimertinib in rats. The results provide a reference for the clinical concomitant medications of Rg3 and osimertinib.